2018
DOI: 10.1016/j.bja.2018.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nebulised dexmedetomidine, ketamine, or midazolam for premedication in preschool children undergoing bone marrow biopsy

Abstract: NCT02935959.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 28 publications
(36 reference statements)
2
60
1
Order By: Relevance
“…These findings are consistent with those in previous reports. 5,19 Emergence delirium in children is still considered a mysterious complication after sevoflurane anesthesia. However, recent findings have demonstrated that dexmedetomidine premedication is effective in reducing emergence delirium and PONV in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with those in previous reports. 5,19 Emergence delirium in children is still considered a mysterious complication after sevoflurane anesthesia. However, recent findings have demonstrated that dexmedetomidine premedication is effective in reducing emergence delirium and PONV in children.…”
Section: Discussionmentioning
confidence: 99%
“…First, the indicated timing of premedication administration is 30 min before general anesthesia according to the pharmacodynamics data and the literature. 5,19 Although, the latest pharmacokinetics study has shown that the median time needed for intranasal dexmedetomidine to achieve peak concentration is 37 min, and the maximal sedative effect is observed 45 min after dosing. 23 This might lead to awaken some dexmedetomidine-sedated patients during mask induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dexmedetomidine (Dex)is an a 2 -adrenoreceptor agonist that has found increasing clinical use-for lung protection, for gentle emergence from anesthesia, as an analgesic, as an adjuvant to local anesthetics during regional anesthesia, and even as a supplemental sedative/anxiolytic (Barends et al, 2017;Nguyen et al, 2017). In the last few years, some studies have shown that nebulized Dex administration may allow minimal systemic effects and rapid drug absorption through the respiratory mucosa (Zanaty & El Metainy, 2015;Abdel-Ghaffar et al, 2018). Although nebulized drug administration may be preferred through pulmonary delivery, there are currently no data describing the nebulized effects of Dex on arterial oxygenation during OLV.…”
Section: Introductionmentioning
confidence: 99%
“…Nebulized respiratory administration may results in maximizing the surface area of absorption, less drug loss and increased clinical effectiveness (Wolfe & Braude, 2010). In pediatric populations, it has been demonstrated nebulized Dex (as a premedicant) significantly improved cannulating conditions such as parental separation, face mask acceptance and IV placement (Abdel-Ghaffar et al, 2018), with no hemodynamic side-effects (Zanaty & El Metainy, 2015;Abdel-Ghaffar et al, 2018). However, these studies were often applied to pediatric populations.…”
mentioning
confidence: 99%